UPAYA PREVENTIF TERHADAP STUNTING DAN ANEMIA MELALUI SOSIALISASI DI POSYANDU REMAJA DESA SIBANG KAJA KECAMATAN ABIANSEMAL KABUPATEN BADUNG - N.W.S.P. Sari; L.P.M. Wijayanti; I.P.E.D.M. Putra; A.A.P.R. Dhania; F.M. Perdana; K.T. Adhi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Adolescence is a period of transition from childhood to adulthood, with a variety of health and nutrition problems issues. Based on Basic Health Research (RISKESDAS) 2018, nutritional issues that occur in adolescence include anemia and stunting. This makes it critical to begin nutrition education at a young age in order to prepare for current health conditions as well as future parents. Based on this, it is necessary to have community service activities aimed at providing nutritional information to prevent anemia and stunting through Youth Posyandu, as well as measuring the health condition of adolescents. The method consisted of information on how to prevent stunting and anemia through socialization materials, including anthropometric measurements (height, weight, and upper arm circumference (LILA), and blood pressure checks on 30 adolescents in Sibang Kaja Village, Abiansemal District, Badung Regency. The results of community service activities show an increase in the average knowledge before and after being given the material, although there is no significant difference (p> 0.05). Suggest that it will continue to provide socialization regarding the prevention of stunting and anemia by involving the active participation of youth as youth Posyandu cadres. Keywords: Anemia, posyandu, adolescent, socialization, stunting